COUNSELING OF REVITALIZATION PLAN FOR SUPPORTING FACILITIES AND INFRASTRUCTURE WITH USER-FRIENDLY CONCEPT AT THE AREA OF RW 07 KEBON KACANG, TANAH ABANG, JAKARTA - Martinus Bambang Susetyarto; Anindita Ramadhani; Marselinus Nirwan Luru; Hanidya Chantika; Rosianti Citra Puspa Dewi; Christopher Edho Sanjoyo; Roy Pratama (International Journal of Engagement and Empowerment, 2022)
This article describes community service activities by a team of lecturers and students from the Department of Urban Planning and the Department of Architecture, Universitas Trisakti. The activity started with a site planning study project in the odd semester of the 2021-2022 academic year, with the topic of site planning in one of the Rukun Warga (RW) areas which has an area of ​​+/- 2 HA, with a user-friendly site planning concept. At the beginning of the study, students conducted a physical survey and a cognitive survey of residents regarding the mapping of the RW 07 area, Kelurahan Kebon Kacang, Kecamatan Tanah Abang, Central Jakarta. In this way, residents are trained to express themselves through simple sketches about the physical boundaries, site characteristics, and the treasures of facilities and infrastructure that exist in the RW 07 area. The results of this first work are used as a conceptual basis for user-friendly site planning. The next study work was to design a site plan in RW 07, which was prepared according to user-friendly theory in site planning, the site plan standard, and directions of the Spatial Plan for Trade and Services Zones according to Presidential Decree No. 60/2020. The results of the analysis, synthesis, planning and designing of the RW 07 area was compiled was an academic manuscript to be donated to the RW 07 Planning Forum, Kelurahan Kebon Kacang through this activity. The team succeeded in counseling substances of the design of the RW 07 area, according to the needs of citizens. In addition, the team was successfully measuring the level of empowerment of residents were participating in the community service activity which was held on March 14, 2022 on the neighborhood road in front of the RW 07 Secretariat.